Nasal immunization with AMH-INH-RFRP DNA vaccine for improving follicle development and fertility in buffaloes - Chen, Chao; Zhao, Xuhong; An, Zhigao; Ahmad, Muhammad Jamil; Niu, Kaifeng; Zhang, Xinxin; Nie, Pei; Tang, Jiaomei; Liang, Aixin; Yang, Liguo (Frontiers in Endocrinology, 2023)
Introduction Inhibin DNA vaccine has already been proven to improve the fertility of animals. This study aimed to investigate the effects of a novel Anti-Müllerian hormone (AMH)-Inhibin (INH)-RF-amide-related peptides (RFRP) DNA vaccine on immune response and reproductive performance in buffalo. Methods A total of 84 buffaloes were randomly divided into four groups and nasally immunized twice a day with 10 ml of either AMH-INH-RFRP DNA vaccines (3 × 1010 CFU/ml in group T1, 3 × 109 CFU/ml in group T2, and 3 × 108 CFU/ml in group T3) or PBS (as a control) for 3 days, respectively. All animals received a booster dose at an interval of 14 days. Results ELISA assay revealed that primary and booster immunization significantly increased the anti-AMH, anti-INH, and anti-RFRP antibody titers in the T2 group compared with that in the T3 group. After the primary immunization, the antibody positive rate was significantly higher in the T2 group than that in the T3 group. In addition, ELISA results indicated that concentrations of E2, IFN-γ, and IL-4 were significantly higher in the antibody-positive (P) group compared to the antibody-negative (N) group. In contrast, there was no significant difference in the concentrations of P4 between the P and N groups. Ultrasonography results revealed a highly significant increase of 2.02 mm in the diameter of ovulatory follicles in the P group compared to the N group. In parallel, growth speed of dominant follicles was significantly higher in the P group than that in the N group (1.33 ± 1.30 vs 1.13 ± 0.12). Furthermore, compared to N group, the rates of oestrus, ovulation, and conception were also significantly higher in the P group. Conclusion The novel AMH-INH-RFRP DNA vaccine improves the proportion of oestrus, ovulation, and conception in buffalo by promoting the production of E2 and the growth of follicles.